Evaluation of Interleukin-22 and Toll-like receptor-2 as an Immunological Biomarkers in Breast Cancer Patients - Ikram Khazal Qasim Al-Hasso (مجله كليه طب الكندي, 2024)
Background: Interleukin-22 is an effector cytokine belongs to the IL-10 family. Signaling of this cytokine control tumor development by boosting cancerous cells growth. Toll-like receptor-2 act key function in activation of tumor cell proliferation besides increasing tumor cell invasion.